1991
DOI: 10.1002/j.1556-6676.1991.tb01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Counselor Self‐Reference in the Therapeutic Dyad

Abstract: Ninety‐one male and female counselors completed a survey assessing the frequency of their use of self‐referent statements (positive and negative self‐disclosure and positive and negative self‐involving responses) in individual counseling. As the researchers hypothesized, counselors reported using a significantly greater frequency of positive versus negative self‐reference. Contrary to hypotheses, there were no significant differences due to either counselor gender or level of counseling experience alone. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Those who espouse a humanistic orientation posit that therapist self-disclosure illustrates therapists' genuineness and positive regard for clients (Robitschek & McCarthy, 1991) and renders the therapeutic process less mysterious (Kaslow, Cooper, & Linsenberg, 1979). Followers of the humanistic tradition, in fact, advocate that therapists' realness and authenticity are vital to promoting clients' openness, intimacy, trust, selfunderstanding, and change (Rogers, 1951;Truax & Carkhuff, 1967).…”
Section: Disclosures Of Immediacymentioning
confidence: 95%
See 1 more Smart Citation
“…Those who espouse a humanistic orientation posit that therapist self-disclosure illustrates therapists' genuineness and positive regard for clients (Robitschek & McCarthy, 1991) and renders the therapeutic process less mysterious (Kaslow, Cooper, & Linsenberg, 1979). Followers of the humanistic tradition, in fact, advocate that therapists' realness and authenticity are vital to promoting clients' openness, intimacy, trust, selfunderstanding, and change (Rogers, 1951;Truax & Carkhuff, 1967).…”
Section: Disclosures Of Immediacymentioning
confidence: 95%
“…Existing research indicates that the most frequent topics of disclosure relate to professional background (e.g., degree, therapy style, and training) whereas less frequent content includes sexual practices and beliefs (Edwards & Murdock, 1994;Geller & Farber, 1997;Robitschek & McCarthy, 1991). More specifically, Edwards and Murdock (1994) found that their 184 licensed, doctoral-level psychologist participants, most of whom espoused an eclectic orientation, reported the following pattern of disclosure, from most to least frequent: professional issues (e.g., degree, experience), success/failure, interpersonal relations, attitudes, personal feelings, and sexual issues.…”
Section: Use Appropriate Content In Therapist Self-disclosuresmentioning
confidence: 99%
“…In addition to defining counselor self-disclosure, it is also important to examine when and why professionals choose to disclose. Robitschek and McCarthy (1991) found that according to 91 surveyed master's and doctoral level counselors, self-disclosures of all types (e.g., demographics, beliefs, experiences) were more likely to occur when the disclosure indicated a similarity between the client and the counselor in terms of experiences or feelings. In surveys, counselors have indicated that they most frequently use self-disclosure to achieve a variety of immediate counseling goals, which include fostering the therapeutic alliance, serving as a model of appropriate behavior, normalizing client experiences, and increasing perceived similarity between themselves and their clients (Edwards & Murdock, 1994).…”
Section: Counselor Self-disclosurementioning
confidence: 96%
“…Commonly disclosed counselor information as reported by 400 surveyed psychologists also includes sexual orientation, personal and professional success or failure in life experiences, interpersonal relationships, attitudes (e.g., politics, religion, personal likes/dislikes), and personal feelings such as happiness or anger (Edwards & Murdock, 1994). Least likely self-disclosures are those that address sexual or intimate topics (Edwards & Murdock, 1994;Robitschek & McCarthy, 1991). In addition to defining counselor self-disclosure, it is also important to examine when and why professionals choose to disclose.…”
Section: Counselor Self-disclosurementioning
confidence: 98%
“…There is an existing body of research on self-disclosure by therapists working with individuals (Fox, Strum, & Walters, 1984;Mahrer, Fellers, Durak, Gervaize, & Brown, 1981;Mathews, 1988;Nilsson, Strassberg, & Bannon, 1979;Robitschek & McCarthy, 1991;Rosie, 1980). There is an existing body of research on self-disclosure by therapists working with individuals (Fox, Strum, & Walters, 1984;Mahrer, Fellers, Durak, Gervaize, & Brown, 1981;Mathews, 1988;Nilsson, Strassberg, & Bannon, 1979;Robitschek & McCarthy, 1991;Rosie, 1980).…”
Section: Researchmentioning
confidence: 99%